2016
DOI: 10.1186/s12864-016-3218-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of SNP genotypes to identify carriers of harmful recessive mutations in cattle populations

Abstract: BackgroundSNP (single nucleotide polymorphisms) genotype data are increasingly available in cattle populations and, among other things, can be used to predict carriers of specific mutations. It is therefore convenient to have a practical statistical method for the accurate classification of individuals into carriers and non-carriers. In this paper, we compared – through cross-validation– five classification models (Lasso-penalized logistic regression –Lasso, Support Vector Machines with either linear or radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Combining results from inference and predictions, especially if leveraging data resampling techniques, is a powerful approach to detecting more robust signals of associations. In the field of genomics, combining results from GWAS and from genomic predictions has been proposed to address the issue of spurious genetic marker-phenotype associations and produce more meaningful results 47 49 or, reverting perspective, to increase the accuracy of genomic predictions 50 . Especially if the accuracy of predictions is high, selected variables from predictive models are likely to play a role in the studied phenotype, and can effectively contribute to identifying robust biomarkers associated with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Combining results from inference and predictions, especially if leveraging data resampling techniques, is a powerful approach to detecting more robust signals of associations. In the field of genomics, combining results from GWAS and from genomic predictions has been proposed to address the issue of spurious genetic marker-phenotype associations and produce more meaningful results 47 49 or, reverting perspective, to increase the accuracy of genomic predictions 50 . Especially if the accuracy of predictions is high, selected variables from predictive models are likely to play a role in the studied phenotype, and can effectively contribute to identifying robust biomarkers associated with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…These positive responses to selection on fertility traits support the efficiency of genomic selection, even for low-heritable traits. In addition, since the recessive lethal haplotypes were first identified by VanRaden et al (2011), these deleterious mutations have been routinely scanned and removed from the dairy population (Cooper et al, 2014;Biffani et al, 2015;Biscarini et al, 2016;Schütz et al, 2016), which can help further increase the fertility of dairy cattle. Despite the success of genomic selection in improving economically important traits in dairy cattle, there are potential negative effects of genomic selection, including the hindrance of developing resilient cattle and loss of diversity, that may negatively affect the long-term selection responses (Notter, 1999;Hayes et al, 2009).…”
Section: Genomic Improvement Of Fertility Traits In Us Dairy Cattlementioning
confidence: 99%
“…Over the past two decades, both microsatellite and SNP markers have contributed to the development of diagnostic testing of genetic defects and DNA-based parentage (Van Marle-Koster et al, 2013 ). SNP arrays are widely applied in routine genotyping for genomic selection in several farm animal species providing an added advantage of using these genotypes for detection and prediction of carriers of genetic defects (Biscarini et al, 2016 ). Different methods have been reported for prediction that include haplotype-based predictions (Pirola et al, 2013 ) and discriminant analyses (Biffani et al, 2015 ).…”
Section: Application Of Genomics In South Africamentioning
confidence: 99%
“…Different methods have been reported for prediction that include haplotype-based predictions (Pirola et al, 2013 ) and discriminant analyses (Biffani et al, 2015 ). Studies have shown that the accuracy of prediction for the genetic defects could be comparable when using genotypes generated with lower density (Bovine LD) versus a higher density 54K Bovine SNP array (Biscarini et al, 2016 ). The availability of genotypes furthermore provide the potential for identification of beneficial genes such as the Celtic variant of the POLLED gene for homozygous polled animals (Medugorac et al, 2012 ).…”
Section: Application Of Genomics In South Africamentioning
confidence: 99%